Electrical stimulation of the cuneiform nucleus enhances the effects of rehabilitative training on locomotor recovery after incomplete spinal cord injury - Scheuber, Myriam I.; Guidolin, Carolina; Martins, Suzi; Sartori, Andrea M.; Hofer, Anna-Sophie; Schwab, Martin E. (Frontiers in Neuroscience, 2024)
Most human spinal cord injuries are anatomically incomplete, leaving some fibers still connecting the brain with the sublesional spinal cord. Spared descending fibers of the brainstem motor control system can be activated by deep brain stimulation (DBS) of the cuneiform nucleus (CnF), a subnucleus of the mesencephalic locomotor region (MLR). The MLR is an evolutionarily highly conserved structure which initiates and controls locomotion in all vertebrates. Acute electrical stimulation experiments in female adult rats with incomplete spinal cord injury conducted in our lab showed that CnF-DBS was able to re-establish a high degree of locomotion five weeks after injury, even in animals with initially very severe functional deficits and white matter lesions up to 80–95%. Here, we analyzed whether CnF-DBS can be used to support medium-intensity locomotor training and long-term recovery in rats with large but incomplete spinal cord injuries. Rats underwent rehabilitative training sessions three times per week in an enriched environment, either with or without CnF-DBS supported hindlimb stepping. After 4 weeks, animals that trained under CnF-DBS showed a higher level of locomotor performance than rats that trained comparable distances under non-stimulated conditions. The MLR does not project to the spinal cord directly; one of its main output targets is the gigantocellular reticular nucleus in the medulla oblongata. Long-term electrical stimulation of spared reticulospinal fibers after incomplete spinal cord injury via the CnF could enhance reticulospinal anatomical rearrangement and in this way lead to persistent improvement of motor function. By analyzing the spared, BDA-labeled giganto-spinal fibers we found that their gray matter arborization density after discontinuation of CnF-DBS enhanced training was lower in the lumbar L2 and L5 spinal cord in stimulated as compared to unstimulated animals, suggesting improved pruning with stimulation-enhanced training. An on-going clinical study in chronic paraplegic patients investigates the effects of CnF-DBS on locomotor capacity.